Sickle Cell Nephropathy and Associated Factors among Asymptomatic Children with Sickle Cell Anaemia - Uchenna Modestus Nnaji; Christian Chukwukere Ogoke; Henrietta Uche Okafor; Kingsley I. Achigbu (Hindawi Limited, 2020)
Background. Sickle cell nephropathy (SCN) is a serious complication of sickle cell anaemia (SCA) with asymptomatic onset in childhood and possible progression to chronic kidney disease (CKD). In Southeast Nigeria, few studies have evaluated renal function in paediatric SCA patients for early detection of renal impairment and early intervention to reduce morbidity and mortality. Therefore, this study evaluated the renal function of paediatric SCA patients in a steady state based on glomerular filtration rate and urinalysis findings (proteinuria and haematuria). Methods. A cross-sectional study of consecutively recruited sixty haemoglobin SS (HbSS) children in a steady state and sixty age- and sex-matched haemoglobin AA (HbAA) controls aged 2-18 years was done. Renal function of HbSS subjects was evaluated using estimated glomerular filtration rate (eGFR) which was compared with healthy HbAA subjects. The prevalence of significant proteinuria and haematuria, its association with eGFR, and the effect of past sickle cell crisis (in the preceding 24 months) on renal function were also evaluated. Results. Mean eGFR was significantly higher in HbSS subjects than in the HbAA subjects (p=0.001) and decreased with age. Significant proteinuria and haematuria were more prevalent in the HbSS group (3.4% and 6.7%, respectively) compared to the HbAA subjects (0% and 0%, respectively) (p=0.496 and 0.119, respectively). No significant association was observed between eGFR and proteinuria (p=1.000) or haematuria (p=1.000). There was a positive correlation between eGFR and frequency of past painful crisis that required hospitalization (r=0.138, p=0.295) and between eGFR and frequency of blood transfusion (r=0.679, p≤0.001). Conclusions. Asymptomatic paediatric HbSS (SCA) patients had higher mean eGFR indicating an increased risk of nephropathy. There was no association between eGFR and proteinuria or haematuria. Frequent sickle cell crises especially one requiring transfusion were positively correlated with hyperfiltration.